Estudo da analgesia induzida por administração de antagonista de receptores NMDA – Comparação entre a administração central (intratecal) e periférica (gânglio da raiz dorsal) em modelos de dor e hiperalgesia em ratos - Araújo, Diego Fernandes de (2019)
NMDA receptor antagonists are widely used as analgesics in medical practice, however, their side effects, related to their performance at central receptors, limit their wide use. Spinal NMDA receptors are involved in central sensitization processes in chronic and neuropathic pain situations. On the other hand, a recent study evidenced an unprecedented activation mechanism of these receptors in the periphery, in dorsal root ganglia, dependent on type C fibers, in an inflammatory pain model. Thus, in the present study the objective was to evaluate the peripheral receptors participation in the analgesic effect induced by the AP-5 antagonist in different models of nociception and hyperalgesia. Intraganglionar AP-5 administration was shown to have equivalent analgesic effects to those presented by intrathecal injection of the same antagonist in all the models tested. At nociception tests induced by capsaicin and formalin injections in rat paws we observed similar analgesic effects both using intraganglionar or intrathecal routes of NMDAR antagonist pretreatment, as well as in the tests of carrageenan-induced hyperalgesia and neuropathy by sciatic nerve constriction. However, we did not observe the same analgesic effect in the post-surgical hyperalgesia experiment. In view of these results, we conclude that NMDA receptor antagonists may have their analgesic effect, in whole or in part, due to the blockade of peripheral receptors. Thus, the study broadens the understanding of the mechanisms involved in pain processing and opens new perspectives for the use of drugs that act at peripheral level, reducing central side effects.